1991
DOI: 10.1152/jappl.1991.70.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild-to-moderate airflow limitation on exercise capacity

Abstract: To determine the effect of mild-to-moderate airflow limitation on exercise tolerance and end-expiratory lung volume (EELV), we studied 9 control subjects with normal pulmonary function [forced expired volume in 1 s (FEV1) 105% pred; % of forced vital capacity expired in 1 s (FEV1/FVC%) 81] and 12 patients with mild-to-moderate airflow limitation (FEV1 72% pred; FEV1/FVC % 58) during progressive cycle ergometry. Maximal exercise capacity was reduced in patients [69% of pred maximal O2 uptake (VO2max)] compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 0 publications
8
122
0
7
Order By: Relevance
“…Thus, we have reaffirmed earlier findings that were published more than a decade ago. 4,8,10 However, the most tantalizing findings dealt with the association between body weight and asthma, an association that has become the focus of more-recent interest and scrutiny. Obese children with asthma comprised nearly half of the study subjects and were overrepresented in the group who tallied higher scores when the degree of impairment due to asthma was calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we have reaffirmed earlier findings that were published more than a decade ago. 4,8,10 However, the most tantalizing findings dealt with the association between body weight and asthma, an association that has become the focus of more-recent interest and scrutiny. Obese children with asthma comprised nearly half of the study subjects and were overrepresented in the group who tallied higher scores when the degree of impairment due to asthma was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…9 First, the degree of resting airflow obstruction could determine the ventilatory limits for aerobic exercise. 10 Second, the degree of bronchial hyperresponsiveness could impose limitations on exercise tolerance, an effect separate from baseline airway caliber. 11 Finally, the level of habitual activity could affect physical fitness, as is the case in healthy adults.…”
mentioning
confidence: 99%
“…Pacientes que possuem grau de obstrução pulmonar elevado podem limitar as atividades físicas, porém a atividade física não exerce influência na variável VEF 1 dos indivíduos com DPOC (12)(13)(14) . Esse fato concorda com a literatura pertinente, reafirmando que a prática de exercícios aeróbios em programas de reabilitação não influenciam no grau de obstrução pulmonar e, sim, nos distúrbios secundários à DPOC (15) .…”
Section: Resultsunclassified
“…In contrast, individuals with pulmonary disease commonly exhibit pulmonary flow limitation, often experiencing it even at rest (Dueck, 2000). Babb et al (1991) found that 11 of 12 subjects with abnormal pulmonary function exhibited flow limitation during maximal exercise, with 7 of the 12 exhibiting some degree of flow limitation at rest.…”
Section: Flow-volume Relationshipmentioning
confidence: 98%
“…Graphs can be generated for different intensities of exercise, with the tidal flow-volume loops produced during exercise plotted within a larger reference expiratory flow-volume loop obtained from a maximal breathing maneuver during rest. This method has been widely used to assess the degree of expiratory flow limitation and ventilatory constraint (Aaron et al, 1992;Babb et al, 1991;Chapman et al, 1998;Derchak et al, 2000;Grimby, 1969;Johnson et al, 1991aJohnson et al, ,b, 1992Johnson et al, , 1995Marciniuk et al, 1994;McClaran et al, 1999;Martinez et al, 1996;Mota et al, 1999;Regnis et al, 1996;Stubbing, 1980a). Indeed, Bye et al (1983) suggest that pulmonary flow-volume characteristics are perhaps the most important determinant of exercise limitation because of their implications for matching ventilation to metabolic demand.…”
Section: Flow-volume Relationshipmentioning
confidence: 99%